Types and Density of Aquatic Plant in the Watas Hutan Lake, Tanjung Balam Village, Siak Hulu Sub-regency, Kampar Regency, Riau Province - Maya Lestari; Efawani '; Deni Efizon (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Watas Hutan Lake is one of the oxbow lakes in the Kampar regency. This lake is overgrown by various types of water plants that almost cover the surface of the lake. This condition hamper the fishing activities in the lake. This research aims to discover the types and density of the aquatic plant in the lake and it was conducted from February to March 2015. Field sampling was done 2 times, a month period. The plants were then identified based on Van Steenis (1981).Result shown that there were 7 species of aquatic plants present and they are belonged to 4 classes, 7 families. They are Eichhornia crassipes, Pandanus sp., Colocasia sp., Cyperus sp., Ipomoea aquatica, Paspalum sp., and Salvinia natans. The most common plant Salvinia natans (37.6-56 organisms/m2, relative density 22.4-43.1 %), while the rarest was Ipomoea aquatica (3.3-27 organisms/m2, relative density 2.5-14.1 %). In general, the relative density of aquatic plants in the Watas Hutan Lake can be categorized as rare to medium.Keyword: Aquatic Plant, Density, Watas Hutan Lake